Imitation and inspiration in public sector reform: lessons from commonwealth experiences - Laking, rob; Norman, Richard (2007)
This article is based on a paper originally presented at the 2006 Conference of the Commonwealth Association of public administration and management. It discusses case studies of reform in developing countries presented at the commonwealth Advanced Seminar, held annually in Wellington, New Zealand. The cases are analysed in terms of major reform issues such as civil service reform, strategic planning, management decentralization and accountability for results to draw out similarities in challenges and responses across jurisdictions and also some lessons about the uptake and implementation of policy ideas from other governments. The case illustrate the influence on developing country governments of public management ideas, ranging from specific imitation of new management `technologies' to more generalized inspiration of the possibilities of reform. - Reproduced.
Keywords: Public administration; Administrative reform